PENGARUH PELATIHAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT TELEKOMUNIKASI INDONESIA WITEL SAMARINDA - Rita Utami; Robiansyah Robiansyah; Syaharuddin Y Syaharuddin (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2020)
Rita Utami. 2018. The Effect of Training and Organizational Culture on the Performance of Employees of PT Telekomunikasi Indonesia Witel Samarinda, under guidance. As Advisor I, Mr. Robiansyah and Mr. Syaharuddin Y As Advisor II.The purpose of this study is to examine the effect of training and organizational culture on the performance of employees of PT Telekomunikasi Indonesia Witel Samarinda. Research data collection uses a census method in which all populations of 70 people is sampled. This study uses multiple linear regression analysis with SPSS as a calculation tool.The results of the study show that there is a positive and significant influence of Training on Employee Performance. And there is a positive and significant influence of Organizational Culture on Employee Performance.